Structure and functions of Mer, an innate immune checkpoint - Ubil, Eric; Zahid, Kashif Rafiq (Frontiers in Immunology, 2023)
Immunotherapy is a promising therapeutic tool that promotes the elimination of cancerous cells by a patient's own immune system. However, in the clinical setting, the number of cancer patients benefitting from immunotherapy is limited. Identification and targeting of other immune subsets, such as tumor-associated macrophages, and alternative immune checkpoints, like Mer, may further limit tumor progression and therapy resistance. In this review, we highlight the key roles of macrophage Mer signaling in immune suppression. We also summarize the role of pro-inflammatory (M1) and anti-inflammatory (M2) phenotypes in tumor onset and progression and how Mer structure and activation can be targeted therapeutically to alter activation state. Preclinical and clinical studies focusing on Mer kinase inhibition have demonstrated the potential of targeting this innate immune checkpoint, leading to improved anti-tumor responses and patient outcomes.